PERUBAHAN NILAI KEKERASAN DAN KONDUKTIVITAS LISTRIK ALUMINIUM AKIBAT PROSES EQUAL CHANNEL ANGULAR PRESSING (ECAP) - Rusnaldy, Rusnaldy; Iskandar, Norman; Rais, Muhammad Khairul; Erlangga, Wisnu Tri (ROTASI, 2014)
In current study, Equal Channel Angular Pressing (ECAP) process was applied to pure aluminium rod. The effect of the number of passes on hardness and electrical conductivity ECAP samples was investigated. The dimensions of ECAP die for 12 mmm diameter workpieces are designed with intersect angle of 120o. The experiments were carried out by using samples cut from an ingot and a rod and machined to a size of 12 mm in diameter and 50 mm in length. The workpiece was pressed into the ECAP die up to 7 passes at room temperature.After deformation, all samples were subjected to a hardness test, an electrical conductivity test and for optical microscope study. The hardness measurement of the ECAP samples suggested that enhanced hardness would be obtained by repeating ECAP process.Increasing the electrical conductivity of the ECAP samples indicatesthat there is no dislocation formation due to increasing plastic deformation in ECAP process